PAEDIATRIC HEPATIC HAEMANGIOMA-A RARE CAUSE OF PYREXIA OF UNKNOWN ORIGIN - Nasir, Hanana; Bashir, Hassan; Asghar, Iqra; Tahir, Iqra; Seerat, Iqtadar (Journal of Ayub Medical College Abbottabad, 2024)
Pyrexia of unknown origin (PUO) has remained a diagnostic challenge for medical professionals for decades as its aetiology remains elusive and requires extensive investigation. Hepatic Haemangioma (HH) is generally not considered a possible cause of PUO. HH is the most frequent, non-cancerous tumor in children usually presents as vague abdominal pain. We describe a case of 4-year-old female presented with the complaint of dull abdominal pain associated with low grade fever. Extensive workup was done to find out the cause. Her haemoglobin also dropped suggestive of bleeding haemangioma. She was treated with steroids (prednisolone) which significantly reduced her inflammatory markers prior to surgery. Later, hepatectomy was done. The surgery was uneventful, and her PUO was also resolved.